Engineering of Push‐Pull Thiophene Dyes to Enhance Light Absorption and Modulate Charge Recombination in Mesoscopic Solar Cells. (1st November 2012) - Cai, Ning; Wang, Yinglin; Xu, Mingfei; Fan, Ye; Li, Renzhi; Zhang, Min; Wang, Peng
Abstract The elaborate selection of diverse π‐conjugated segments which bridge the electron donors and acceptors in organic push‐pull dyes can not only tune the molecular energy‐levels but also impact the interfacial energetics and kinetics of dye‐sensitized solar cells (DSCs). In this paper, a series of triphenylamine‐cyanoacrylic acid photosensitizers is reported with TT, EDOT‐BT, EDOT‐CPDT, and CPDT‐EDOT (herein TT, EDOT, BT, and CPDT denote terthiophene, ethylenedioxythiophene, bithiophene, and cyclopentadithiophene, respectively) as the π‐linkers, and the dye‐structure correlated photocurrent and photovoltage features of DSCs based on a cobalt electrolyte are scrutinized via analyzing light absorption and multichannel charge transfer kinetics. Both stepwise incorporation of more electron‐rich blocks and rational modulation of connection order of dissimilar segments can result in a negative movement of ground‐state redox potential and a red‐shift of the absorption peak. While these styles of reducing energy‐gap do not exert too much influence on the electron injection from photoexcited dye molecules to titania, the dyestuff employing the EDOT‐BT linker presents a faster interfacial charge recombination and a slower dye regeneration, accounting for its inferior cell efficiency of 5.3% compared to that of 9.4% at the AM1.5G conditions achieved by the CPDT‐EDOT dye.